2010
DOI: 10.1007/s12170-009-0069-9
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Proteomics: Identifying New Drug Targets and Biomarkers by Understanding Functionality

Abstract: Recent proteomics studies on human plasma high-density lipoprotein (HDL) have discovered up to 50 individual protein constituents. Many of these have known functions that vary surprisingly from the lipid transport roles commonly thought to mediate HDL's ability to protect from coronary artery disease. Given newly discovered roles in inflammation, protease inhibition, complement regulation, and innate immunity, many have begun to view HDL as a broad collection of distinct particle subfamilies, each distinguishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 46 publications
3
25
0
1
Order By: Relevance
“…The enrichment of distinct proteins in HDLs in various diseases states evolves as an important determinant for associations between HDL function and cardiovascular risk (16,30,45). Our improved understanding of the composition of HDLs can enable pharmacologic attempts in manipulating HDL composition and function to reduce cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enrichment of distinct proteins in HDLs in various diseases states evolves as an important determinant for associations between HDL function and cardiovascular risk (16,30,45). Our improved understanding of the composition of HDLs can enable pharmacologic attempts in manipulating HDL composition and function to reduce cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…HDLs are a family of heterogeneous particles that vary 4-fold in cholesterol content (28,29) and carry a protein cargo of .50 different proteins (30,31). The protein composition of HDLs emerges as important determinant when investigating the association between HDL function or concentration and CVD (30,32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, two-dimensional electrophoresis studies by Asztalos and colleagues (18), as well as our own work (11,19), strongly support the concept that certain apolipoproteins segregate among different HDL particles. These observations present the intriguing possibility that the phospholipids of HDLs act as an organizing platform that facilitates the assembly of specific protein complexes (20). Such subspecies could have important functional implications in the context of CVD protection, inflammation, or even innate immune function.…”
mentioning
confidence: 99%
“…[293][294][295] Recent proteomic analysis of high density lipoprotein-cholesterol (HDL) particles, which are inversely correlated with the incidence of CVD, have revealed new HDL-associated proteins and suggested that the particles of different composition may have different cardioprotective activity. 296,297 Plasma proteomic approach has been applied to identify new biomarkers in acute myocardial infarction (AMI). Serum levels of apolipoprotein J (ApoJ) have been downregulated and have been less glycosylated in patients with newonset AMI compared to control individuals.…”
Section: Proteomics and Metabolomicsmentioning
confidence: 99%